Effect of combination polymers of natural and semi synthetic origin on the drug release of Flavoxate. HCl: Design and Characterization of gastro retentive floating tablets for Flavoxate.HCl. - Gunda, Raghavendra Kumar; Manchineni, Prasada Rao; Sudireddy, Rajini (International Pharmacy Acta, 2021)
The objective of current work is to study the effect of combination of macromolecules (polymers) of natural (Lannea coromandelica gum) and semi synthetic (HPMCK100M) origin on the drug release of Flavoxate.HCl from the Gastro retentive floating formulation. Flavoxate.HCl, an antispasmodic agent. Mainly used for treating urinary incontinence, urgency of urination. Floating tablets of Flavoxate.HCl were prepared using variable composition of HPMCK100M, Lannea coromandelica gum (LCG) with effervescent mixtures by direct compression technique. 9 formulations were made and evaluated for quality control parameters. From the obtained results clears that all formulations passes the compendial limits. Data obtained from the dissolution study fitted well to kinetic modeling, kinetic parameters were determined. GRFX5 composed of 40 mg of HPMCK100M & 40 mg of LCG, is the best formulation showing similarity f2=84.66, f1= 4.29 with the marketed product (URISPAS). Formulation GRFX5 follow first order, whereas release mechanism found to be nonfickian type (n= 0.77).